2021
DOI: 10.3390/v13061149
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Knowledge about Role of Pets in Zoonotic Transmission of SARS-CoV-2

Abstract: Pets play a crucial role in the development of human feelings, social life, and care. However, in the era of the prevailing global pandemic of COVID-19 disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), many questions addressing the routes of the virus spread and transmission to humans are dramatically emerging. Although cases of SARS-CoV-2 infection have been found in pets including dogs, cats, and ferrets, to date there is no strong evidence for pet-to-human transmission or s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 70 publications
(91 reference statements)
2
43
0
1
Order By: Relevance
“…Previous research reported that two of 15 dogs kept in households with confirmed human COVID-19 cases in Hong Kong were infected with SARS-CoV-2 [ 13 ]. Since then, SARS-CoV-2-infected dogs have been reported worldwide [ 1 , 3 ]. Under experimental conditions, cats and ferrets are reported to be susceptible to the virus, while dogs are less susceptible [ 12 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research reported that two of 15 dogs kept in households with confirmed human COVID-19 cases in Hong Kong were infected with SARS-CoV-2 [ 13 ]. Since then, SARS-CoV-2-infected dogs have been reported worldwide [ 1 , 3 ]. Under experimental conditions, cats and ferrets are reported to be susceptible to the virus, while dogs are less susceptible [ 12 ].…”
mentioning
confidence: 99%
“…Under experimental conditions, cats and ferrets are reported to be susceptible to the virus, while dogs are less susceptible [ 12 ]. However, almost as many dogs as cats have been naturally infected [ 1 , 3 , 11 ], possibly because people interact more with their dogs than with cats [ 11 ]. Although domestic dogs are often considered family members, few reports have been published on the SARS-CoV-2 seroprevalence in dogs.…”
mentioning
confidence: 99%
“…Similarly, the relatively weak effects of keeping other animals (rodents and pigs) on the risk of a more severe course of Covid-19 were probably just artifacts of multiple tests. It must be, however, reminded that hamsters are susceptible to the SARS-CoV-2 infection 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging studies have shown that the disease can also be transferred from infected humans to animals, such as domestic and nondomestic animals [ 20 ]. Bats are reservoirs for SARS-CoV [ 21 ] and other CoVs related to MERS-CoV and SARS-CoV [ 22 ]. Therefore, bats are the most likely potential reservoir with a possible intermediate transmission event in pangolins for SARS-CoV-2 [ 23 ].…”
Section: Covid-19 In Animalsmentioning
confidence: 99%
“…These signs appeared a week after the cat owner self-quarantined at home due to COVID-19 [ 20 ]. Subsequently, consecutive cases of SARS-COV-2 in cats were reported in several countries [ 22 ]. Cats with COVID-19 are usually asymptomatic or have mild to moderate respiratory and gastrointestinal symptoms [ 24 ].…”
Section: Covid-19 In Animalsmentioning
confidence: 99%